Farmers' intentions to adopt Triple S for sweetpotato seed conservation - Mayanja, S.; Mutiso, J.M.; Kwikiriza, N.; Okello, J.J.; Hareau, G.; Ssekandi, J. (Informa UK Limited, 2024)
In Uganda, farmers in arid and semi-arid areas lack sweetpotato seed after dry spells. This constrains the crop’s potential to contribute to food security. Triple S (sand, storage, sprouting) is a root-based technology addressing seed scarcity. Despite the technology’s efficacy, a systematic assessment of its demand has not been done. A study was undertaken to assess how Knowledge, Attitudes, Norms and Perceptions influence farmers uptake of the Triple S, using a structured questionnaire with 255 farmers stratified into users (n = 132) and non-users (n =123). Sex-disaggregated focus groups were conducted with 40 farmers. The Theory of Planned Behavior and Technology Adoption Model were used to test hypotheses on Triple S adoption. Perceived Behavior Control, Perceived Usefulness and Knowledge positively predicted Behavior Intention (BI) only for non-users, while Attitude, Subjective Norms and Agency predicted BI for users. Gender Norms negatively influenced Agency for both groups. Gender-responsive adoption strategies may enhance technology uptake.